Multicellular Tumor Spheroids as an in Vivo–Like Tumor Model for Three-Dimensional Imaging of Chemotherapeutic and Nano Material Cellular Penetration - Hui-li Ma; Qiao Jiang; Siyuan Han; Yan Wu; Jin Cui Tomshine; Dongliang Wang; Yaling Gan; Guozhang Zou; Xing-Jie Liang (Molecular Imaging, 2012)
We present a flexible and highly reproducible method using three-dimensional (3D) multicellular tumor spheroids to quantify chemotherapeutic and nanoparticle penetration properties in vitro. We generated HeLa cell–derived spheroids using the liquid overlay method. To properly characterize HeLa spheroids, scanning electron microscopy, transmission electron microscopy, and multiphoton microscopy were used to obtain high-resolution 3D images of HeLa spheroids. Next, pairing high-resolution optical characterization techniques with flow cytometry, we quantitatively compared the penetration of doxorubicin, quantum dots, and synthetic micelles into 3D HeLa spheroid versus HeLa cells grown in a traditional two-dimensional culturing system. Our data revealed that 3D cultured HeLa cells acquired several clinically relevant morphologic and cellular characteristics (such as resistance to chemotherapeutics) often found in human solid tumors. These characteristic, however, could not be captured using conventional two-dimensional cell culture techniques. This study demonstrated the remarkable versatility of HeLa spheroid 3D imaging. In addition, our results revealed the capability of HeLa spheroids to function as a screening tool for nanoparticles or synthetic micelles that, due to their inherent size, charge, and hydrophobicity, can penetrate into solid tumors and act as delivery vehicles for chemotherapeutics. The development of this image-based, reproducible, and quantifiable in vitro HeLa spheroid screening tool will greatly aid future exploration of chemotherapeutics and nanoparticle delivery into solid tumors.